SELF-REPORTED DENTURE SATISFACTION IN COMPLETELY EDENTULOUS PATIENTS - N. Abdulla Mardan; Cristina Teodora Preoteasa; Marina Imre; Ana Maria Tancu; Elena Preoteasa (Romanian Journal of Oral Rehabilitation, 2014)
This study focuses on understanding the completely edentulous patient’s condition in terms of satisfaction with conventional complete dentures, the most common treatment alternative. Study objectives were: to identify the major reasons of patients’ dissatisfaction with conventional complete denture; to determine how they are linked to some anatomical, physiological and treatment related factors; to assess patients’ satisfaction with newly made complete dentures. Material and methods An observational study was conducted on a convenience sample of 94 completely edentulous patients having an average age of 69 years. Data collection was done through interviews supplemented by an objective clinical examination, functional evaluation and photographic analysis. Results Patients’ main complaints were related to masticatory difficulties (83%) and instability of the denture (72.3%). Complaints related to mastication were mainly observed in male patients over 65 years, with skeletal Class II, first-time wearers of prosthesis. Most dissatisfied about denture’s stability were male patients over 65, who have lost their teeth because of periodontal disease, with severe ridge resorption and higher degree of treatment difficulty. Conclusions Knowledge of the reasons of dissatisfaction with the old, soon to be replaced, complete dentures, can help the dentist to better understand individual treatment need and obtain an increased quality of the medical outcome. Also, it can help determine when other treatment alternative is more suitable.